Obstacle avoidance robot applying fuzzy control system - Chia Woon, Liew (2014)
This project primarily addresses the design and implementation of fuzzy logic based controller for obstacles avoidance robot. Some techniques, sensors and controller have been applied to fulfill the requirements of the robot. The robot able to interact with an unknown environment using a reactive strategy determined by the sensors information. The obstacle avoidance controller is a two inputs and two outputs system. The inputs are two proximity measurement of the obstacles distance, and the outputs are the velocities of the two wheels. The robot is driven by two independent DC motors. The ultrasonic sensors are mounted at left, front and right side of the mobile robot. It can detect the obstacles within the range 3 cm to 300 cm. The kinematic model was developed to control the movement of the robot’s wheels. The detection of the obstacles by the sensors activates the controller which simply attempts to avoid the robot with the obstacles. Once the robot avoids the obstacles, the robot will keep sense for the new environment. Based on these signals, the controller control the velocity of left and right wheels thus making the robot to move forward and turning at the same time, i.e., the robot avoid the obstacle by turn left with left motor velocity is 6.57 cm/s, right motor velocity is 8.29 cm/s and angular velocity is 0.066154 rad/s when the obstacle detected from left sensor is 100 cm, right sensor is 100 cm and front sensor is 50 cm. Different obstacles distance orientation also been tested and the robot response is working as expected.